P04.02 Partner notification in north america: a historical account. (13th September 2015) - Sobanjo, O; Steben, M; Cheuk, E; Kettner, J; Fast, M; Meadwick, H
Abstract : Introduction: Partner notification (PN) has been an integral part of sexually transmitted infection (STI) prevention for decades. Initially proposed for syphilis control, it now extends to a wide range of STI. NCCID PN project included documenting its origins in North America (NA). Methods: A multi-pronged approach has been adopted due to paucity of historical evidence. Literature search: electronic database (PubMed), manual reference list search, printed literature on public health (PH) history in NA, search of significant PH organisation websites for related publications. Semi-structured interviews of key participants in STD control programs National STD prevention conference in Minnesota. Blogging: obtain historical accounts through use of online discussion sites or focus groups e.g. stdpreventiononline.org Request of materials: participants in the online blog and those for the structured interviews were to bring memorabilia, documents, letters. Results: PN might have been in use since the 19th century, PN has been shown effective when implemented as part of a larger PH initiative. Crucial to its success was the monitoring of performance. Confidentiality was a priority. Identifiers were used in reports to make it possible to trend networks and patterns. PN evolved in time with changes in diseases. Efforts were made to make available free services for testing and treatment. The costs implications favoured adoption of methods such as provider-referral and patient-referral. Given the importance of PN to STI prevention, it was disappointing to find limited documentation published particularly in Canada compared to United States. Conclusion: PN has been touted as the cornerstone in STI control. Looking at its origins and principles of success helps informs decisions regarding its current role and practice. Prevailing circumstances such as restricted budgets, high rates of mobility and increasing numbers of anonymous partners call for a modification in the use of PN today. Newer models employing social media are being developed. Disclosure of interest statement: The National Collaborating Centre for Infectious Diseases is funded by the Public Health Agency of Canada. No pharmaceutical grants were received in the development of this study.